EFEKTIVITAS KOOPERATIF NUMBERED HEADS TOGETHER TERHADAP PEMAHAMAN MATEMATIS PADA MATERI GEOMETRI BANGUN DATAR PESERTA DIDIK KELAS III SEKOLAH DASAR - Muhammad Faizal; Rayi Siti Fitriani; Cristin Martha Dewi Sartika; Siti Halimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical understanding, particularly in plane geometry, remains a challenge for elementary school students. Therefore, an instructional approach that actively engages students in the learning process is needed. This study aimed to examine the effectiveness of the Numbered Heads Together (NHT) cooperative learning model in improving the mathematical understanding of third-grade elementary school students on plane geometry concepts. The study employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest design. The participants consisted of 23 third-grade students from SDN Rosela Indah selected through total sampling. Data were collected using a short-answer mathematical understanding test administered before and after the implementation of the NHT model. Data analysis included descriptive statistics, the Shapiro–Wilk normality test, and the Wilcoxon Signed-Rank Test. The findings revealed that the mean score increased from 52.61 on the pretest to 80.00 on the posttest. All students demonstrated improved performance, with no participant showing a decline in scores. The Wilcoxon Signed-Rank Test indicated a statistically significant difference between the pretest and posttest results (Z = –4.220, p < 0.001), confirming the effectiveness of the NHT model in enhancing students' mathematical understanding. These findings suggest that the Numbered Heads Together cooperative learning model is an effective instructional strategy for fostering active participation, collaboration, and conceptual understanding of plane geometry among elementary school students.